Social Workers Preparation to Ethno-social Work: Theoretical Substantiation and Efficiency Checking Criteria - Banugul Zh. Abdrasheva, Zhanar Kh. Kendirbekova, Galina G. Chernaya, (Opción, 2019)
This paper is devoted to various aspects of ethnosocial work as a way to achieve ethnosocial stability in society. This article provides consideration of ethnic sentiments and various socialization problems of certain categories of migrants based on rich factual material – re-emigrants, immigrants and refugees. Social worker training efficiency is considered in terms of readiness to ethnosocial work. Wherein, such components of specialist’s readiness to work with ethnosocial groups as personality-motivational, informative and operational are fully disclosed. The author has developed an experimental course program based on theoretical statements of this study, which was tested in the Buketov Karaganda State University.